Advancing a cross-cultural understanding of teacher perceptions of school climate: A latent class analysis using 2018 TALIS data - Zhao, Mingren; Jin, Rui (Frontiers in Psychology, 2023)
In recent years, school climate has increasingly received research attention. Most studies have focused only on student perceptions of school climate, whereas little is known regarding teachers’ views, and cross-country comparisons are scarce. To advance cross-country understanding of teacher perceptions of school climate, this study used data from the 2018 Teaching and Learning International Study (TALIS) to explore latent classes of teacher perceptions and compared differences between Ameri-can, Finnish, and Chinese teachers. Latent class analysis revealed that a four-class solution was the most appropriate for each teacher subsample: positive participation and teacher-student relation, positive teacher-student relation, moderate, and low participation for the U.S. and China datasets, while positive teacher-student relation, moderate, negative discipline, and low participation for the Finland dataset. However, measurement invariance across countries was violated. We further investigated the impact of predictors on latent classes of teacher perceptions of school climate. The results revealed varied patterns of cross-cultural differences across countries. Our findings implied that a more reliable and valid scale of teacher perceptions of school climate for cross-country comparison is needed. Tai-lored interventions are necessary as more than half of teachers perceived moderate and less desired school climate, and educators should consider cultural differences when drawing on experiences from other countries.